A study on the effectiveness SPUS (Skim Pembangunan Usahawan Siswazah) among higher learning institution students in Kota Kinabalu / Hamdi Haris - Haris, Hamdi (2009)
A study on the effectiveness SPUS (Skim Pembangunan Usahawan Siswazah) among higher learning institution students in Kota Kinabalu City.